Pemakaian kode tutur bahasa Jawa oleh pedagang di pasar - Erlin Kartikasari (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Language as a means of human interaction is related to human speech acts, especially in the use and selection of language when communicating. Traders in the market are identical to using certain language codes to sell their goods to attract buyers. Using speech codes during buying and selling transactions shows the trader's self-identity in the market environment. Market traders use various speech codes to talk to buyers. This paper focuses on the speech codes the traders use to convince customers. This research uses a descriptive qualitative research method. The research data source comes from the speech of market traders, especially herbal medicine traders in the Magetan Market. The data were collected with the support of recording, note-taking, and interview techniques. The data analysis starts by grouping the speech data based on the speech code used and then analyzing the speech code based on the problem formulation. The results of this study show that traders in the market interacting with buyers use speech codes of Javanese 'ngoko' and 'krama' and Indonesian. In addition, jamu sellers also code-switch and code-mix in communicating with buyers.